2007
DOI: 10.1364/ol.32.001017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on spectral loss characteristics of subwavelength terahertz fibers

Abstract: By measuring the spectral loss characteristics of subwavelength-diameter terahertz fibers, our study supports the recent theory proposed by M. Sumetsky [Opt. Lett. 31, 870 (2006)] that diameter-variation-induced radiation is a dominant loss mechanism for subwavelength fibers in the low- (<1%) core-fraction-power regime. This physical mechanism limits the lowest guidable frequency in a subwavelength fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…For the arbitrary wavelength λ and refractive index n of the microfiber, the smallest possible radius of the waveguiding microfiber is found as From Figure 4, the threshold corresponds to a change in the microfiber radius of only several nanometers, which indicates a significant variation of the transmission spectrum with nanoscale change of the microfiber radius. These predictions have found excellent experimental confirmation both for the silica microfibers considered in the next subsection and for THz fibers [29].…”
Section: How Thin Can a Microfiber Be And Still Guide Light?supporting
confidence: 52%
“…For the arbitrary wavelength λ and refractive index n of the microfiber, the smallest possible radius of the waveguiding microfiber is found as From Figure 4, the threshold corresponds to a change in the microfiber radius of only several nanometers, which indicates a significant variation of the transmission spectrum with nanoscale change of the microfiber radius. These predictions have found excellent experimental confirmation both for the silica microfibers considered in the next subsection and for THz fibers [29].…”
Section: How Thin Can a Microfiber Be And Still Guide Light?supporting
confidence: 52%
“…Several methods towards this have been proposed. One strategy first demonstrated by Chen et al is to use a subwavelength core surrounded by an air cladding [7,8]. In order to further reduce the loss, a porous structure of sub-wavelength holes can be introduced into the already sub-wavelength solid core of the fiber [10][11][12][13][14][28][29][30], as first predicted numerically by Hassani et al [10,28] and then demonstrated by Dupuis et al [29] and later Atakaramians et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although theory predicts lower losses for the porous fibers, we are unable to distinguish between the already very small losses of the porous and non-porous fibers within the error of our experimental setup. As we demonstrate in the following section the transmission peak (bell-shaped transmission curve) results from the balance between absorption loss (at high frequencies), scattering loss (at low frequencies), 9 and frequency dependent coupling loss.…”
Section: Transmission and Loss Measurementsmentioning
confidence: 73%
“…Experimentally measured transmission spectra through subwavelength fibers all feature bell-like profiles with frequencies of the transmission maxima defined by the competition between several loss mechanisms such as coupling, material absorption, and scattering on fiber imperfections 9,12 . Particularly, at higher frequencies, both the absorption loss and coupling loss increase substantially leading to a decrease in the fiber transmission (see Figures 3(c,g), and Figures 4 (b,c), for example).…”
Section: Theoretical Modelingmentioning
confidence: 99%
See 1 more Smart Citation